Phage-derived Hol49_Lys19/sodium alginate/chitosan composite green coating: Preparation, performance and preservation effect on refrigerated salmon - Shuxuan Li; Jing Li; Ming Zhang; Rundong Wang; Xiaoni Wang; Chunyan Li; Defu Zhang (Food Microbiology, 2027)

High-precision extraction and dynamics of thermokarst lakes in the Three Rivers Source Region using the SVM coupled edge-OTSU based on Sentinel-1 data - Wangping Li; Rongqi Wan; Xiaodong Wu; Xiaoqiang Cheng; Yadong Liu; Yanjun Bian; Heng Du; Niu Wang; Wenbo Wei; Zhaoye Zhou; Xiuxia Zhang; Defu Zou (CATENA, 2026)

Elevated hydrostatic pressure promotes organic carbon mineralization in reservoir sediments - Yan Zhang; Shangbin Xiao; Defu Liu; Wenjun Yang; Huiqun Cao; Jia Liu; Chenghao Wang; Li Zhu; Shijian Li; Shiping Lai; Xinghui Xia (Water Research, 2026)

Physics-informed machine learning of hyporheic exchange driven by channel blockage and riverbed morphodynamics - Hang Li; Linlin Li; Defu Liu; Genguang Zhang; Jiahao Zou; Yu Lei; Canyong Li (Journal of Hydrology, 2026)

Characterization of the overall quality, flavor compounds, sensory analysis, and microbial community of huangjiu co-fermentation with Rhodotorula mucilaginosa and Saccharomyces cerevisiae - Mengzhu Yu; Changpeng Li; Gaopo Li; Defu Zhang; Zhangyi Feng; Dongliang Reng; Jun Qiu; Song Fang; Yuzong Zhao (Food Research International, 2026)

Parameterization of ground ice dynamics in permafrost models: Advances, challenges, and future directions - Yifan Wu; Guojie Hu; Lin Zhao; Zhe Sun; Bowen Zhang; Yao Xiao; Defu Zou; Guangyue Liu; Xiaofan Zhu; Tonghua Wu; Xiaodong Wu; Wenxin Zhang; et al. (Earth-Science Reviews, 2026)

Soil texture regulates soil C mineralization by C substrates and microbial characteristics under vegetation restoration - Lingbo Dong; Weifang Hu; Defu Wang; Hailong Zhang; Jianzhao Wu; Jiwei Li; Rula Sa; Zhouping Shangguan; Lei Deng (Plant and Soil, 2026)

Experimental Investigation into the Influence of Water Saturation on the Tensile Failure Behavior of Diaspore-Type Bauxite: Implications for Underground Mining of Bauxite - Defu Zhu; Wenshuo Hu; Yalin Li; Qingsheng Bai; Yongjie Jia; TengFei Fu; Gan Feng; Yujiang Zhang; Xiaosong Sun; Yongqing Lin; Dingwei Sun (Rock Mechanics and Rock Engineering, 2026)

Influence of Fracture Geometry Parameters on the Mechanical Properties and Spatiotemporal Crack Evolution in Granite: Insights from Integrated AE and DIC Monitoring - Xiangyu Wang; Lei Zhang; Defu Zhu; Chunwang Zhang; Ze Wang; Zhenting Lv; Chengke Yang; Yu Zhang (Rock Mechanics and Rock Engineering, 2026)

Multi-component dissolved gas dynamics as early warning indicators for algal bloom development in the three gorges reservoir - Chenyu Wei; Dian Li; Hao Li; Yanan Huang; Xiaojuan Guo; Hao Zhang; Danli Deng; Defu Liu; Zhengjian Yang (Water Research, 2026)

In-situ radical polymerization for solid polymer electrolytes in lithium-ion batteries: a comprehensive review - Yong Luo; Churu Zhang; Ya Liao; Zhitian Ding; Defu Li; Lufa Zhu; Hao Luo; Beiyuan Liu; Jiali Guo; Xiaoli Peng; Shipai Song; Yong Xiang; et al. (Chemical Engineering Journal, 2026)

Structural disparity-driven heterogeneity in iron-catalyzed biomass pyrolysis: graphitization mechanisms of hemicellulose and lignin - Defu Shi; Chen Zhang; Sunwen Xia; Yingquan Chen; Haiping Yang (Fuel, 2026)

Manipulation of autophagy regulates mitochondrial homeostasis and early embryo development of cryopreserved porcine oocytes - Jiehuan Xu; Mengqian He; Jun Gao; Lingwei Sun; Caifeng Wu; Shushan Zhang; Defu Zhang; Jianjun Dai (Animal Reproduction Science, 2026)

Gp8 mediates adsorption of bacteriophage vB_VpP_jzsmvpa to the host Vibrio parahaemolyticus - Shuxuan Li; Xiaoni Wang; Jing Li; Ming Zhang; Ke Liu; Xuepeng Li; Jianrong Li; Chunyan Li; Defu Zhang (Antonie van Leeuwenhoek, 2026)

The discovery of natural-product inhibitors targeting white spot syndrome virus dUTPase (WSV112) through virtual screening and bioassays - Shangming Ran; Yuting Fu; Xiaolong Xue; Yueling Zhang; Defu Yao; Guanghui Chen (Aquaculture, 2026)

The crucial role of ground ice in slowing permafrost degradation - Guojie Hu; Zhe Sun; Lin Zhao; Deliang Chen; Defu Zou; Chien-Lu Ping; Wenxin Zhang; Yao Xiao; Guangyue Liu; Ren Li; Xiaodong Wu; Yifan Wu; et al. (Science Bulletin, 2026)

Acid-triggered degradation of a silicon-based nanopesticide activates SA-dependent conifer defense against Dioryctria sylvestrella - Zheng Wang; Antong Ma; Jiaxing Fang; Xiaoqi Xu; Wei Gan; Jiayue Liu; Fu Liu; Sufang Zhang; Defu Chi; Dafeng Chen; Yapei Wang; Xiangbo Kong (Pesticide Biochemistry and Physiology, 2026)

Policy-driven distinct dust pollution patterns in a super-large magnesite mining area: Spatiotemporal analysis integrating satellite remote sensing and CALPUFF model - Baodong Ma; Ting Kang; Shuxian Gao; Shuai He; Defu Che; Yuansheng Zhang (Journal of Cleaner Production, 2026)

High-resolution (30 m) mapping of permafrost distribution in the Genhe River Basin, Greater Khingan Mountains, Northeast China - Xueling Jiao; Lin Zhao; Defu Zou; Lingxiao Wang; Chong Wang; Yuanwei Wang; Guojie Hu; Erji Du; Yao Xiao; Guangyue Liu; Shibo Liu; Yuxin Zhang; et al. (Journal of Mountain Science, 2026)

Multifactorial impacts on ash behaviors during oxy-fuel co-combustion of semi-coke and biomass - Jinping Zhang; Wenwen Wei; Haichen Zhao; Siyuan Li; Jingchun Shen; Defu Che; Lei Chen (Fuel, 2026)

NO heterogeneous reduction during oxy-fuel combustion of semi-coke: The role of high-temperature rapid gasification - Pengqian Wang; Chenxi Zhang; Xingpeng Li; Jiaojiao Zhang; Yi Liu; Yongbo Du; Chang’an Wang; Defu Che; Bo Bai (Fuel, 2026)

Two-phase structure matching strategy promotes formation of built-in electric fields in Eu-Co3O4/NiFe LDH heterojunction for anion exchange membrane water electrolysis - Wenjun Zhang; Xiaohui He; Jian Huang; Defu Chen (Chemical Engineering Journal, 2026)

Mito-boosting nanovesicle hydrogel dressing rescues hepatocyte bioenergetic insufficiency and promotes post-hepatectomy regeneration - Yixiao Pan; Le Ding; Tangansu Zhang; Changjie Yang; Huimin Wu; Xiandong Zeng; Yingqiang Liang; Defu Kong; Shihang Yu; Yiwen Chen; Siyuan Pan; Hongye Wang; et al. (Chemical Engineering Journal, 2026)

Retraction notice to “Targeted delivery of honokiol by zein/hyaluronic acid core-shell nanoparticles to suppress breast cancer growth and metastasis” [Carbohydr. Polym. 240 (2020) 116325 - Qi Zhang; Jing Wang; Dan Liu; Wenquan Zhu; Shuang Guan; Li Fan; Defu Cai (Carbohydrate Polymers, 2026)

Metallic Contaminants and Osteoporosis: a Review of the Gut-Bone Axis - Yongjie Yang; Shuqi Yuan; Tianbao Gong; Jiaxiang Zhang; Haitao Ma; Defu Yu; Tao Chen (Biological Trace Element Research, 2025)

Control of backfill ratio in a short-wall green-intelligent mining working face to prevent pollution from coal-based solid waste: experimental and design studies on the relationship between two-dimensional images and volume of gangue - Yun Zhang; Yixuan Yang; Xingping Lai; Shenggen Cao; Yongzi Liu; Mingbo Chi; Defu Zhu; Baiyi Li; Di Wang; Jifeng Li (Journal of Cleaner Production, 2025)

Lattice Boltzmann simulation on adsorption of sulfuric acid vapor by ash particles - Jiyun Ren; Chongjun Jiang; Fangfang Hu; Hui Wang; Yunhao Shao; Xinyu Liu; Zhang Wu; Feng Pan; Qidong Yang; Lei Deng; Defu Che (Fuel, 2025)

Redox diverse Co+2/Co+3 species embedded 3D nanoconfined silica walls as an efficient catalyst for fast oxidative desulfurization of fuel oil - Mateen Ahmad; Usman Ali; Afaq Nazir; Xiaoqi Liu; Haoran Sun; Haonan Zhang; Defu Yin; Alieu Kamara; Hanbao Li; Zhen Liu; Zifeng Yan (Fuel, 2025)

Corrigendum to “Hyaluronic acid-modified liposomal honokiol nanocarrier: Enhance anti-metastasis and antitumor efficacy against breast cancer” [Carbohydr. Polym. 235 (2020) 115981] - Jing Wang; Dan Liu; Shuang Guan; Wenquan Zhu; Li Fan; Qi Zhang; Defu Cai (Carbohydrate Polymers, 2025)

Research and Application of the Calculation Method for Vertical Stress of Interlayer Rock in Coal Mining Under Pillar Goaf - Qian Wang; Yujiang Zhang; Guorui Feng; Defu Zhu; Fudong Ma; Wushuai Hao; Shule Li; Shuai Zhang (Rock Mechanics and Rock Engineering, 2025)

Preliminary analysis of a slow-moving high-locality landslide in the Zagunao River Basin, Sichuan Province, China - Shengsen Zhou; Weile Li; Huiyan Lu; Zhou Xu; Wenlong Yu; Shanmiao Xu; Pan Zhang; Chunhao Wei; Yusen Li; Defu Wang; Weiwei Zhan; Qiang Xu (Bulletin of Engineering Geology and the Environment, 2025)

A probabilistic formula for sediment incipient motion on combined sloping beds by considering the hiding-exposure effect - Linlin Li; Hang Li; Genguang Zhang; Yao Xiao; Defu Liu; Yu Lei; Maohua Le (Hydrological Sciences Journal, 2025)

Study on the mechanism of multiple sodium salts co-loading on ash fusibility and mineral evolution behaviors - Hongli Liang; Jinhao Yi; Yang Yang; Lei Zhang; Tao Ma; Weibin Chen; Hu Liu; Defu Che (Fuel, 2025)

Characterization of volatile flavour compounds and characteristic flavour precursors in poultry eggs based on multi-omics and machine learning - Hongqiang Li; Xiangmin Zhao; Xiaoming Li; Jing Liang; Shizhen Qin; Jinlu Li; Aiwen Zhang; Linna Xu; Defu Tang; Fuwei Li (Food Chemistry, 2025)

Earthworms multifacetedly drive size- and type-dependent microplastic transport in soils - Xiaoting Zhang; Yan Liu; Defu He (Environmental Pollution, 2025)

A coupled model of surface water-groundwater interaction with the effect of riverbed deformation in the alluvial channel - Linlin Li; Hang Li; Genguang Zhang; Defu Liu; Yao Xiao; Ying Liu; Jiahao Zou (CATENA, 2025)

Preparation of carbon nanosheet from molten salts assisted pyrolysis of biomass towards to carbon-negative technology - Sunwen Xia; Chen Zhang; Rui Fang; Yong Wang; Defu Shi; Bin Li; Dong Wang; Kuihua Han; Haiping Yang (Fuel, 2025)

Promising eco-friendly agents targeting Pseudomonas fluorescens biofilms - Xiaoli Chen; Defu Zhang; Xuefei Liu; Jianrong Li; Lu Wang; Xue Bai (Food Bioscience, 2025)

Corrigendum to “Inhibition of growth and metastasis of breast cancer by targeted delivery of 17-hydroxy-jolkinolide B via hyaluronic acid-coated liposomes” [Carbohydr. Polym. 257 (2021) 117572] - Dan Liu; Qi Zhang; Jing Wang; Shuang Guan; Defu Cai; Jicheng Liu (Carbohydrate Polymers, 2025)

Research on Ship Engine Fuel Consumption Prediction Algorithm Based on Adaptive Optimization Generative Network - Defu Zhang; Yuxuan Song; Jianfeng Gao; Zhenyu Shen; Liangkuan Li; Anren Yao (Journal of Marine Science and Engineering, 2025)
With the long-term operation of ships, the performance of marine diesel engines gradually declines due to the wear of internal moving components, increasing the risk of potential failures. Fuel consumption is a critical indicator for assessing engine operating conditions, and accurately predicting baseline fuel consumption under normal operating conditions is essential for evaluating ship energy efficiency and conducting fault diagnosis. To address common issues in marine engine operational data, such as noise pollution, missing values, inconsistent scales, and feature redundancy, a Diesel Engine Data Enhancement and Optimization Framework (DEOF) was developed to systematically improve data quality. Furthermore, to overcome the limitations of existing models, such as insufficient prediction accuracy and poor stability under complex operating conditions, a Meta-learning Diffusion Residual Attention Network (MD-RAN) is proposed. This approach leverages the strengths of diffusion models in nonlinear generative modeling, integrates meta-learning mechanisms to enhance task adaptation speed, employs multi-head attention modules to strengthen feature extraction, and incorporates dynamic residual connections to improve training stability and flexibility. The data used in this study were collected from real-world operations of ocean-going vessels, ensuring high representativeness. This paper systematically benchmarks the proposed model with the traditional learning model. The results are verified to be effective. The MD-RAN algorithm is significantly better than the original model in terms of prediction accuracy, stability, and nonlinear expression ability. The R2 value can reach 0.9853, and the RMSE and MAE are as low as 1.5801 and 1.1879, respectively. Its feasibility will be further evaluated in practical applications in the future. This study not only provides a systematic data-driven modeling framework, offering technical insights for constructing high-quality datasets, but also establishes a novel generative modeling approach for marine diesel engine fuel consumption prediction, providing robust support for intelligent engine maintenance and energy efficiency optimization.

Study on NO formation and ash characteristics during co-combustion of semi-coke and biomass under O2/CO2 conditions - Jinping Zhang; Jingchun Shen; Junyi Fang; Lei Chen; Chang’an Wang; Defu Che (Fuel, 2025)

Ground surface deformation in permafrost region on the Qinghai-Tibet Plateau: A review - Shibo Liu; Lin Zhao; Lingxiao Wang; Lin Liu; Defu Zou; Guojie Hu; Zhe Sun; Yuxin Zhang; Wei Chen; Xueying Wang; Meng Wang; Huayun Zhou; et al. (Earth-Science Reviews, 2025)

Regional landslide identification using the slope unit containing deformation information - Xiaohu Lei; Xiuying Wang; Shaojie Zhang; Hongjuan Yang; Defu Wang; Fangqiang Wei (Natural Hazards, 2025)

Preparation and application of bioadhesive hydrogel powder loaded with quorum sensing inhibitor isomaltitol for salmon preservation - Ke Liu; Ming Zhang; Wutong Bai; Wenjing Yang; Xinran Lv; Xue Bai; Xuepeng Li; Defu Zhang; Jianrong Li (Food and Bioproducts Processing, 2025)

Optimization of enzymatic hydrolysis of collagen and screening and application of hypolipidemic peptide - Yancheng Bi; Ming Zhang; Ke Liu; Xinran Lv; Xuepeng Li; Xue Gao; Fangchao Cui; Defu Zhang; Jianrong Li (Food Bioscience, 2025)

(C6H10N2)ZnX4·H2O (X=Cl and Br): Excellent nonlinear optical properties and temperature induced photoluminescence for encryption - Chuanying Shen; Chenyi Zhang; Qiwei Xing; Defu Sun; Kui Wu; Bingbing Zhang; Jiyang Wang; Duanliang Wang (Chemical Engineering Journal, 2025)

Targeted phytogenic compounds against Vibrio parahaemolyticus biofilms - Xue Bai; Xiaoli Chen; Defu Zhang; Xuefei Liu; Jianrong Li (Critical Reviews in Food Science and Nutrition, 2025)

Simulation study on seasonal recovery of waste heat and water resources in flue gas and slurry after WFGD - Gaofeng Fan; Xinyue Gao; Chang’an Wang; Yujie Hou; Jinming Zhang; Jie Xu; Defu Che (Process Safety and Environmental Protection, 2025)

White spot syndrome virus IE1 protein blocks the integrin-FAK signaling to enhance viral infection in shrimp - Kaiyu Lu; Xiyu Chen; Huimin Zhang; Jinghua Zhu; Yongzhen Zhao; Xiuli Chen; Yueling Zhang; Defu Yao (Fish & Shellfish Immunology, 2025)

Cell Death in Crustacean Immune Defense - Zeyan Chen; Muhammad Tayyab; Defu Yao; Jude Juventus Aweya; Zhihong Zheng; Xianliang Zhao; Zhongyang Lin; Yueling Zhang (Reviews in Aquaculture, 2025)
Cell death mechanisms in crustaceans are a complex interplay of processes essential for maintaining cellular homeostasis and immune defense. Modes of cell death like apoptosis, necroptosis, and necrosis are well‐documented in crustaceans, serving crucial roles in removing damaged or infected cells. Unlike in other organisms, crustaceans likely lack pyroptosis, a type of programmed cell death associated with innate immunity and inflammation, because they do not possess the gasdermin genes essential for this process. Recently, NETosis and ferroptosis have emerged as significant mechanisms in pathogen defense. NETosis, involving the release of DNA fibers and antimicrobial proteins, helps trap and neutralize pathogens, while ferroptosis, an iron‐dependent form of cell death, contributes to lipid peroxidation and immune responses. Cuproptosis, although not yet studied in the context of crustacean immunity, shows potential crosstalk with ferroptosis, particularly in the regulation of metal ion homeostasis, oxidative stress, and cellular metabolism. Understanding these mechanisms offers promising applications in aquaculture, such as developing targeted immune modulators and enhancing disease resistance in economically important crustacean species.

Copper Homeostasis and Its Impact on Innate Immunity in Crustaceans - Hejia Chen; Xi Huang; Muhammad Tayyab; Mingming Zhao; Defu Yao; Zhihong Zheng; Xianliang Zhao; Yongzhen Zhao; Xiuli Chen; Bobo Zhang; Qiongqiong Yang; Yueling Zhang; et al. (Reviews in Aquaculture, 2025)
Copper, an essential micronutrient in crustaceans, plays vital roles in enzymatic processes, oxygen transport, pigmentation, and structural protein synthesis, including collagen and elastin. Recent research has elucidated its pivotal role in innate immunity of crustaceans, enhancing the immune response by promoting phagocytic activity, antimicrobial peptide production, and modulation of immune gene expression. Copper ions exhibit antimicrobial effects by disrupting cell membranes and inhibiting microbial proliferation. Furthermore, copper governs antioxidant defense mechanisms, protecting crustaceans against oxidative stress and infection. However, excessive copper can lead to toxicity, highlighting the need for strict maintenance of copper homeostasis. This review explores the complex processes of copper homeostasis in crustaceans, detailing transport mechanisms, storage proteins, and detoxification pathways. It emphasizes copper's critical physiological and immunological functions, contributing to a comprehensive understanding of its multifaceted roles in crustaceans and laying groundwork for further exploration of copper homeostasis as a strategy for boosting crustacean immunity. Aquaculture practices significantly influence copper levels in crustaceans. Effective copper management, including monitoring techniques, water treatment strategies, and regulatory frameworks, is crucial for both crustacean welfare and environmental sustainability.

Threshold of sediment incipient motion on a three-dimensional riverbed by considering the hiding-exposure effect with experimental investigations - Linlin Li; Yao Xiao; Genguang Zhang; Yu Lei; Hang Li; Defu Liu (Acta Geophysica, 2024)

Experimental study and chemical equilibrium calculation on the mineral transformation of high-alkali coal under oxy-fuel condition - Lin Zhao; Chang’an Wang; Yingchao Nie; Yongxu Chen; Jinming Zhang; Maoyun Luo; Defu Che (Fuel, 2024)

Self-supporting electrodes for high-performance flexible solid-state supercapacitors: Recent advances and perspectives - Yanxin Liao; Defu Tang; Shile Liu; Tianrui Liu; Lingyun Chen; Qichun Zhang (Chemical Engineering Journal, 2024)

Natural grassland restoration exhibits enhanced carbon sequestration and soil improvement potential in northern sandy grasslands of China: An empirical study - Huang Luxi; Gao Yong; Wang Defu; Cui Xiaojing; Zhang Huimin; Yuan Jiamao; Gao Miaomiao (CATENA, 2024)

Facile synthesis of carbon black and sodium alginate based particles system for efficient solar desalination of highly concentrated brine - Jiwen Zhang; Xiaozhen Hu; Kaiyuan Shi; Haiyan Sun; Dejian Yang; Mutian Yang; Bo Xu; Zhengwen Xu; Defu Xu (Journal of Environmental Chemical Engineering, 2024)

OsIPK1 frameshift mutations disturb phosphorus homeostasis and impair starch synthesis during grain filling in rice - Lina Wang; Jing Cui; Ning Zhang; Xueqin Wang; Jingping Su; María Pilar Vallés; Shian Wu; Wei Yao; Xiwen Chen; Defu Chen (Plant Molecular Biology, 2024)

Simultaneous hydroxyapatite-based phosphorus recovery and partial denitrification-anammox-based nitrogen removal during sludge leachate treatment - Ben Dai; Yifeng Yang; Zuobin Wang; Jingzhou Zhou; Xiaodi Li; Yi Yang; Defu Gan; Junxia He; Xin Zhang; Siqing Xia (Journal of Water Process Engineering, 2024)

Preparation of amorphous coal-based activated coke via a two-step process of carbonization and steam activation - Xiaoling Jin; Hui Wang; Hong An; Xiaoming Huang; Wenyan Zhang; Lei Deng; Defu Che (Fuel, 2024)

Efficient synthesis of furfural over mZSM-5@SO42-/mSiO2 core–shell catalyst by targeted regulating B/L acids - Renjie Ji; Defu Yin; Yao Chen; Like Ma; Fanglin Lv; Yuhao Zhang; Zhen Jia; Jingyun Zhang; Mingya Liu; Shitao Yu; Yue Liu (Fuel, 2024)

Influence of the in-stream structures and parameters variation on transient storage - Junxiong Luo; Ying Liu; Defu Liu; Jinghong Feng; Yongsheng Guo; Xunchuan Song; Hanyue Zhang (Ecological Engineering, 2024)

New insight into oxygen vacancy and synergism in CuCeOx catalysts based on the toluene oxidation - Guangtao Hu; Zirui Zhang; Chang’an Wang; Guojie Li; Dandan Zhou; Jinshi Wang; Defu Che; Running Kang (Journal of Environmental Chemical Engineering, 2024)

Highly stereoselective hydrogenation of α‑pinene over Ir nanoparticles confined in SiO2 shells - Defu Yin; Zewei Hu; Mingya Liu; Jingyun Zhang; Hanli Zheng; Yunxi Hou; Shitao Yu; Lu Li; Shiwei Liu; Yue Liu (Chemical Engineering Journal, 2024)

The evolutionary adaptation of shrimp hemocyanin subtypes and the consequences on their structure and functions - Jiaxi Li; Mingming Zhao; Xin Zhang; Zhihong Zheng; Defu Yao; Shen Yang; Ting Chen; Yueling Zhang; Jude Juventus Aweya (Fish & Shellfish Immunology, 2024)

Penaeid shrimp counteract high ammonia stress by generating and using functional peptides from hemocyanin, such as HMCs27 - Mingming Zhao; Zhihong Zheng; Chuanqi Wang; Defu Yao; Zhongyang Lin; Yongzhen Zhao; Xiuli Chen; Shengkang Li; Jude Juventus Aweya; Yueling Zhang (Science of The Total Environment, 2023)

Novel ship fuel consumption modelling approaches for speed and trim optimisation: Using engine data as auxiliary - Kangli Wang; Defu Zhang; Zhenyu Shen; Wei Zhu; Hongcai Ye; Dong Li (Ocean Engineering, 2023)

LamB as a potential negative regulator to the immune response of shrimp Litopenaeus vannamei upon Vibrio parahaemolyticus infection - Xianliang Zhao; Dong Yang; Mingqi Zhong; Zhongyang Lin; Defu Yao; Yueling Zhang (Aquaculture, 2023)

Investigation on Co-combustion characteristics and NO emissions of coal and municipal sludge in a tangentially fired boiler - Chang'an Wang; Meijing Chen; Pengbo Zhao; Lei Zhou; Yujie Hou; Jinming Zhang; Qiang Lyu; Defu Che (Fuel, 2023)

Dynamics and diversity of microbial community in salmon slices during refrigerated storage and identification of biogenic amine-producing bacteria - Yingchang Li; Nan Zhao; Yuanyuan Li; Defu Zhang; Tong Sun; Jianrong Li (Food Bioscience, 2023)

The transcription factor CEBP homolog of Penaeus vannamei contributes to WSSV replication - Chuanqi Wang; Huimin Zhang; Jinghua Zhu; Haiping Liu; Yiqing Yang; Bingbing Sun; Tingchu Wu; Yueling Zhang; Defu Yao (Fish & Shellfish Immunology, 2023)

Water and heat coupling processes and its simulation in frozen soils: Current status and future research directions - Guojie Hu; Lin Zhao; Ren Li; Hotaek Park; Xiaodong Wu; Youqi Su; Georg Guggenberger; Tonghua Wu; Defu Zou; Xiaofan Zhu; Wenxin Zhang; Yifan Wu; et al. (CATENA, 2023)

Combustion characteristic of low calorific gas under pilot ignition condition—Exploring the influence of pilot flame products - Yongbo Du; Meng Xing; Jingkun Zhang; Jinping Zhang; Lei Deng; Defu Che (Fuel, 2023)

Activity enhancement of core–shell Pd@mCeO2 catalysts for phenol hydrogenation to cyclohexanone by tuning metal-support interactions - Defu Yin; Renjie Ji; Jingyun Zhang; Shitao Yu; Lu Li; Shiwei Liu; Long Jiang; Ying Liu; Zhanqian Song; Yue Liu (Fuel, 2023)

Microfiber-loaded bacterial community in indoor fallout and air-conditioner filter dust - Yingxin Chen; Xinyu Li; Wei Gao; Yalin Zhang; Aoyun Mo; Jie Jiang; Defu He (Science of The Total Environment, 2023)

Nanoplastics induce molecular toxicity in earthworm: Integrated multi-omics, morphological, and intestinal microorganism analyses - Ronggui Tang; Dong Zhu; Yongming Luo; Defu He; Haibo Zhang; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Keyi Chen; Yan Yan; Xinghang Lu; Minshen Ying; Tao Sun; et al. (Journal of Hazardous Materials, 2023)

Prominent toxicity of isocyanates and maleic anhydrides to Caenorhabditis elegans: Multilevel assay for typical organic additives of biodegradable plastics - Xinyu Li; Yingxin Chen; Wei Gao; Aoyun Mo; Yalin Zhang; Jie Jiang; Defu He (Journal of Hazardous Materials, 2023)

Catalytic conversion of toluene by biochar modified with KMnO4 - Xiaoling Jin; Kai Zhang; Jiahao Jiang; Zhengrong Zhu; Lei Deng; Defu Che (Fuel, 2023)

Highly efficient conversion of phenol to cyclohexanone on Pd-based catalysts by cobalt doping - Defu Yin; Renjie Ji; Fanglin Lv; Long Jiang; Jingyun Zhang; Mingya Liu; Zhen Jia; Shitao Yu; Ruiyang Zhao; Yue Liu (Fuel, 2023)

Hydrogenation of N-ethylcarbazole with Hydrogen-Methane mixtures for hydrogen storage - Hu Liu; Jingwen Xue; Pengfei Yu; Yankang Zhang; Jinhua Wang; Defu Che (Fuel, 2023)

Environmental fate and impacts of biodegradable plastics in agricultural soil ecosystems - Aoyun Mo; Yalin Zhang; Wei Gao; Jie Jiang; Defu He (Applied Soil Ecology, 2023)

Comparison of the Homology Between Muskrat Scented Gland and Mouse Preputial Gland - Xiangyu Han; Yuanlin Jiang; Nuannuan Feng; Pengcheng Yang; Meishan Zhang; Weijiang Jin; Tianxiang Zhang; Zhixin Huang; Haoxi Zhao; Kexin Zhang; Shuqiang Liu; Defu Hu (Journal of Mammalian Evolution, 2022)

Metabolic reprogramming in crustaceans: A vital immune and environmental response strategy - Zhongyan Wang; Yueling Zhang; Defu Yao; Yongzhen Zhao; Ngoc Tuan Tran; Shengkang Li; Hongyu Ma; Jude Juventus Aweya (Reviews in Aquaculture, 2022)
Most host organisms undergo metabolic changes in response to pathogens, environmental cues or simply to boost their immunity. Metabolic modulation has therefore been exploited by both host and pathogens to outwit the other during host–pathogen interactions. Recent studies have revealed that a growing number of metabolites and metabolic processes in crustaceans are crucial in host–pathogen interactions. Here, we reviewed recent work on metabolic changes during immune response of crustaceans and the metabolic reprogramming that takes place in the host induced by pathogens, environmental cues or as a host strategy to withstand these changes or clear the pathogen. In aquaculture crustaceans, limited studies exist on this subject; hence, we will also highlight themes for possible future research on metabolite reprogramming and how this strategy can be leveraged to improve sustainable aquaculture and enhance crustaceans’ response to pathogens and environmental changes.

Adaptability of organic matter and solid content to Fe2+/persulfate and skeleton builder conditioner for waste activated sludge dewatering - Xiaoran Li; Yafei Shi; Xi Zhou; Lu Wang; Huiqin Zhang; Kewu Pi; Andrea R. Gerson; Defu Liu (Environmental Science and Pollution Research, 2022)

Crop pest recognition using attention-embedded lightweight network under field conditions - Junde Chen; Weirong Chen; Adnan Zeb; Defu Zhang; Yaser Ahangari Nanehkaran (Applied Entomology and Zoology, 2021)

The expanding repertoire of immune‐related molecules with antimicrobial activity in penaeid shrimps: a review - Jude Juventus Aweya; Zhihong Zheng; Xiaoyu Zheng; Defu Yao; Yueling Zhang (Reviews in Aquaculture, 2021)
Shrimps live in a complex aquatic ecosystem with numerous other biotic and abiotic factors, especially pathogenic microorganisms, which require the adaptation of prudent protective and survival strategies. As invertebrates, shrimps reply on humoral and cellular innate immune response mechanisms for protection against pathogens. One integral part of the humoral innate immune defence mechanism involves many biomolecules that are constitutively expressed or induced by pathogens. Shrimps, therefore, produce various biomolecules and secondary metabolites for physiological and pathophysiological purposes, most of which also act as effector molecules in immune‐related functions. A growing number of molecules have been identified as essential constituents of the immune arsenal of biomolecules in penaeid shrimps. This review provides a synthesis of important information on penaeid shrimp‐encoded immune‐related molecules with antimicrobial activities, their molecular regulation and importance in shrimp innate immune response. Research gaps would be identified and proposed research themes emphasized for future studies.

Effects of ammonia on shrimp physiology and immunity: a review - Mingming Zhao; Defu Yao; Shengkang Li; Yueling Zhang; Jude Juventus Aweya (Reviews in Aquaculture, 2020)
The rapid expansion in shrimp farming comes with problems such as inadequate culture technology, disease outbreak, water pollution and other environmental degradation‐related problems. Prominent among these is the level of ammonia, which has been rising steadily in the last couple of years, mainly due to farming practices and other anthropogenic activities, and therefore has had consequent effects on marine life, especially shrimp. While optimal ammonia levels are a good source of nitrogen for marine phytoplankton that increases the level of dissolved oxygen in water as well serves as food for shrimp, high levels of ammonia are harmful to shrimp. When shrimp pond ammonia levels go beyond the tolerance limits, it inhibits chitinase expression, moulting, growth, phenoloxidase and haemolymph antimicrobial activity, thereby attenuating shrimp innate immune response. In this review, we bring together recent information on the effects of ammonia stress on the growth, physiology, biochemistry, ammonia‐metabolizing enzymes and immunity of shrimp. We also propose areas of research that can be explored in the breeding of new ammonia‐tolerant and disease‐resistant shrimp with robust immune and/or physiological systems that could withstand environmental stress and pathogens.

In-depth proteomic profiling of the Singapore grouper iridovirus virion - Defu Yao; Yingfu Liu; Xiuli Chen; Teck Kwang Lim; Lili Wang; Jude Juventus Aweya; Yueling Zhang; Qingsong Lin (Archives of Virology, 2019)

Regulatory Roles of Peroxisomal Metabolic Pathways Involved in Musk Secretion in Muskrats - Meishan Zhang; Shuang Yang; Minghui Shi; Shumiao Zhang; Tianxiang Zhang; Yimeng Li; Shanghua Xu; Muha Cha; Yuping Meng; Shaobi Lin; Juan Yu; Xuxin Li; et al. (The Journal of Membrane Biology, 2019)

Development of matrix solid-phase dispersion coupled with high-performance liquid chromatography for determination of jolkinolide A and jolkinolide B in Euphorbia fischeriana Steud. - Defu Cai; Weiyu Zhai; Qi Zhang; Jianhua Liu; Yu Sun; Lei Liu; Jicheng Liu (Natural Product Research, 2017)

Impacts of low-molecular-weight organic acids on aquatic behavior of graphene nanoplatelets and their induced algal toxicity and antioxidant capacity - Zhuang Wang; Yucheng Gao; Se Wang; Hao Fang; Defu Xu; Fan Zhang (Environmental Science and Pollution Research, 2016)

Air quality improvement during 2010 Asian games on blood coagulability in COPD patients - Zili Zhang; Jian Wang; Meihua Guo; Mingmei Xiong; Qipeng Zhou; Defu Li; Jiaze Shu; Wenju Lu; Dejun Sun (Environmental Science and Pollution Research, 2016)

Purifying capability, enzyme activity, and nitrification potentials in December in integrated vertical flow constructed wetland with earthworms and different substrates - Defu Xu; Jiaru Gu; Yingxue Li; Yu Zhang; Alan Howard; Yidong Guan; Jiuhai Li; Hui Xu (Environmental Science and Pollution Research, 2016)

Acteoside reduces testosterone by inhibiting cAMP, p450scc, and StAR in rat Leydig cells - Shuqiang Liu; Junwen Zhang; Weixuan Li; Tianxiang Zhang; Defu Hu (Molecular & Cellular Toxicology, 2015)

Nutrient spatial pattern of the upstream, mainstream and tributaries of the Three Gorges Reservoir in China - YuLing Huang; Ping Zhang; DeFu Liu; ZhengJian Yang; DaoBin Ji (Environmental Monitoring and Assessment, 2014)

Tocopherol-deficient rice plants display increased sensitivity to photooxidative stress - Defu Chen; Haiwei Chen; Luhua Zhang; Xiaoli Shi; Xiwen Chen (Planta, 2014)

Isolation and characterization of microsatellite loci from Gasterophilus pecorum (Diptera: Gasterophilidae) - Fang Cheng; Jianmei Yang; Dong Zhang; Defu Hu; Hongjun Chu; Jie Cao; Feng Jiang; Lan Bu; Kai Li (Conservation Genetics Resources, 2014)

Transmembrane routes of cationic liposome-mediated gene delivery using human throat epidermis cancer cells - Shaohui Cui; Bing Wang; Yinan Zhao; Huiying Chen; Huiqin Ding; Defu Zhi; Shubiao Zhang (Biotechnology Letters, 2014)